Evaluation Of the Indonesian Languange Training Program at The Defence Languange Training Centre - Santoso, Puji; Sari, Eliana; Karnati, Neti (Journal of Ecohumanism, 2024)
This program is designed to provide Indonesian language briefings to personnel of friendly countries who will take part in training within the Ministry of Defense and the TNI. In addition, this program is one of the flagship programs of the Ministry of Defense, because it is an effective instrument in defense diplomacy. The purpose of this study is to evaluate the implementation of the Indonesian language education and training program at the Ministry of Defense's Badiklat Language Education and Training Center. This study uses a qualitative approach with an evaluative method. This research uses the CIPP (Context, Input, Process, and Product) model developed by Stufflebeam. The data in this study was obtained through observation, in-depth interviews and documentation studies at the Ministry of Defense's Badiklat Language Education and Training Center. The results of this study show that in the context aspect, this program has been designed with a visionary thinking concept based on national interests with a solid background and legal foundation, but the Language Education and Training Center needs to design its organizational vision and mission. In terms of inputs, this program has been well prepared so that this program has adequate carrying capacity. However, it is still necessary to procure information technology experts and physical coaches. The results of the evaluation of the process aspect show that the implementation of this program is running according to plan, both from academic, personality, and physical similarities. The evaluation of the product aspect shows that the success of this program is very satisfactory, namely 100% of students graduate satisfactorily and are able to continue to the next training.